KARAKTERISTIK PAPAN PARTIKEL DARI KULIT KAKAO DAN SERAT PINANG DENGAN VARIASI POLYMERIC METHYLENE DIPHENYL DIISOCYANATE - Putri, Yanandra Amelia; Mahyudin, Alimin (Jurnal Fisika Unand, 2024)
Research has been carried out to analyze the effect of the percentage of polymeric methylene diphenyl diisocyanate (PMDI) on the physical and mechanical properties of particleboard made from cocoa shells and areca fiber. This research uses a ball mill to obtain the particle size that passes through an 80 mesh sieve. The physical properties tested were density and water content, while the mechanical properties tested were flexural strength and compressive strength using the Universal Testing Machine (UTM). The PMDI variations used are 4%, 6%, 8% and 10%. The density values obtained ranged from 0.97-1.13 g/cm3, water content values ranged from 7.3 - 9.11%, compressive strength values ranged from 216.63-285.02 kg/cm2 and flexural strength values ranged from 1713 .97-2235.23 kg/cm2. The best particle board is particle board with a PMDI content of 8%. The water content and compressive strength values of particle board meet SNI 03-2105-2006, but the density and flexural strength values do not meet SNI 03-2105-2006. Based on the density value of the particle board, the particle board produced is a type of high density particle board.